Nonsocial Functions of Hypothalamic Oxytocin. (7th July 2013) - Yang, Hai-Peng; Wang, Liwei; Han, Liqun; Wang, Stephani C.
Abstract : Oxytocin (OXT) is a hypothalamic neuropeptide composed of nine amino acids. The functions of OXT cover a variety of social and nonsocial activity/behaviors. Therapeutic effects of OXT on aberrant social behaviors are attracting more attention, such as social memory, attachment, sexual behavior, maternal behavior, aggression, pair bonding, and trust. The nonsocial behaviors/functions of brain OXT have also received renewed attention, which covers brain development, reproduction, sex, endocrine, immune regulation, learning and memory, pain perception, energy balance, and almost all the functions of peripheral organ systems. Coordinating with brain OXT, locally produced OXT also involves the central and peripheral actions of OXT. Disorders in OXT secretion and functions can cause a series of aberrant social behaviors, such as depression, autism, and schizophrenia as well as disturbance of nonsocial behaviors/functions, such as anorexia, obesity, lactation failure, osteoporosis, diabetes, and carcinogenesis. As more and more OXT functions are identified, it is essential to provide a general view of OXT functions in order to explore the therapeutic potentials of OXT. In this review, we will focus on roles of hypothalamic OXT on central and peripheral nonsocial functions.